Vinorelbine-loaded multifunctional magnetic nanoparticles as anticancer drug delivery systems: synthesis, characterization, and in vitro release study - Ozcan, Zeynep; Yoruc, Afife Binnaz Hazar (BEILSTEIN-INSTITUT, 2024)
In this study, a multifunctional therapeutic agent combining chemotherapy and photothermal therapy on a single platform has been developed in the form of vinorelbine-loaded polydopamine-coated iron oxide nanoparticles. Vinorelbine (VNB) is loaded on the surface of iron oxide nanoparticles produced by a solvothermal technique after coating with polydopamine (PDA) with varying weight ratios as a result of dopamine polymerisation and covalent bonding of thiol-polyethylene glycol (SH-PEG). The VNB/PDA/ Fe3O4 nanoparticles have a saturation magnetisation value of 60.40 emu/g in vibrating sample magnetometry, which proves their magnetisation. Vinorelbine, which is used as an effective cancer therapy agent, is included in the nanocomposite structure, and in vitro drug release studies under different pH conditions (pH 5.5 and 7.4) and photothermal activity at 808 nm NIR laser irradiation are investigated. The comprehensive integration of precise multifunctional nanoparticles design, magnetic response, and controlled drug release with photothermal effect brings a different perspective to advanced cancer treatment research.
Keywords: drug efficacy; iron oxide nanoparticles; photothermal; solvothermal; method; IRON-OXIDE NANOPARTICLES; FE3O4 NANOPARTICLES; NANOTECHNOLOGY; PEGYLATION; STRATEGY; PROGRESS; Science & Technology - Other Topics; Materials Science; Physics